Plan de Desarrollo Comunitario con énfasis en la economía popular y solidaria: herramientas para el fortalecimiento de la gestión de la calidad de vida de las mujeres rurales de la parroquia Achupallas. - Olalla Parra, Yadira Eliana (2023)
ABSTRACT: This research aims to elaborate a Community Development Plan, emphasizing the popular and solidarity economy: tools for strengthening the management of the quality of life of rural women in the Achupallas parish. The research has a mixed approach, a non-experimental and descriptive design, having 51 societies from the Rural Women's Organization of the Achupallas parish as the study population, to whom a survey was applied, and data were chosen for the interview. The five members of the board of directors. The results show the characteristics of the productive activities that the population study is dedicated to and the conditions that determine their quality of life. Based on this information, the products to create sustainable enterprises were identified, and a development plan was prepared where the objectives were defined, which, together with the strategies and goals, concluded in projects destined to strengthen the management of the companies.